Chitosan as an Underrated Polymer in Modern Tissue Engineering - Marta Kołodziejska; Kamila Jankowska; Marta Klak; Michał Wszoła (Nanomaterials, 2021)
Chitosan is one of the most well-known and characterized materials applied in tissue engineering. Due to its unique chemical, biological and physical properties chitosan is frequently used as the main component in a variety of biomaterials such as membranes, scaffolds, drug carriers, hydrogels and, lastly, as a component of bio-ink dedicated to medical applications. Chitosan’s chemical structure and presence of active chemical groups allow for modification for tailoring material to meet specific requirements according to intended use such as adequate endurance, mechanical properties or biodegradability time. Chitosan can be blended with natural (gelatin, hyaluronic acid, collagen, silk, alginate, agarose, starch, cellulose, carbon nanotubes, natural rubber latex, κ-carrageenan) and synthetic (PVA, PEO, PVP, PNIPPAm PCL, PLA, PLLA, PAA) polymers as well as with other promising materials such as aloe vera, silica, MMt and many more. Chitosan has several derivates: carboxymethylated, acylated, quaternary ammonium, thiolated, and grafted chitosan. Its versatility and comprehensiveness are confirming by further chitosan utilization as a leading constituent of innovative bio-inks applied for tissue engineering. This review examines all the aspects described above, as well as is focusing on a novel application of chitosan and its modifications, including the 3D bioprinting technique which shows great potential among other techniques applied to biomaterials fabrication.